Preliminary survey of insect diversity and population abundance during flowering and fruiting season in Mangifera odorata (Kuini) orchard, Sintok, Kedah, Malaysia - Nurin Izzati Mohd Zulkifli,; Siti Noor Aishikin Abdul Hamid,; Saiful Zaimi Jamil,; Zul Helemey Mohamad Sabdin,; Mohd Shukri Mat Ali,; Aimi Athirah Ahmad, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
A preliminary survey of insect population in Kuini (Mangifera odorata) orchard was conducted between February 2016 and May 2016 in MARDI, Sintok, Malaysia. Collection of insects were done using two different methods namely yellow sticky trap (YST) and sweep net. A total of 857 arthropods were collected during flowering season and 1,454 arthropods during fruiting season. Data were analysed using descriptive statistics while mean comparisons were done using t-test. Thysanoptera recorded the highest percentage (31.65%) of total catch during flowering season, while Blattodea and Neuroptera recorded as the lowest with 0.23% respectively. During fruiting season, the highest recorded insect was Diptera (79.92%) while Thysanoptera and Lepidoptera recorded the lowest percentage (0.07%). The Shannon-Weiner diversity index (H’), Simpson Diversity Index (D) and Margalef’s Diversity Index (d) were for insects during flowering season were of 3.01, 0.87 and 12.44 respectively. Conversely, H’, D and d value for insects during fruiting season were 2.61, 0.83 and 7.28 respectively. Results obtained from this study will be used as baseline for future insect pest and biological control related studies.